2006
DOI: 10.1590/s1806-83242006000100009
|View full text |Cite
|
Sign up to set email alerts
|

Study of DNA damage induced by dental bleaching agents in vitro

Abstract: Dental bleaching is a simple and conservative procedure for aesthetic restoration of vital and non-vital discolored teeth. Nevertheless, a number of studies have demonstrated the risk of tissue damage from the contact of these agents with the oral mucosa. In the current study, the genotoxic potential associated with exposure to dental bleaching agents was assessed by the single cell gel (comet) assay in vitro. Chinese hamster ovary (CHO) cells in vitro were exposed to six commercial dental bleaching agents (Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…[7][8][9] The laser light emitting at the visible red spectrum stimulates the respiratory chain in cells under stress, leading to alterations in electron transport by mitochondria. 16,17,19,22,25 Then, besides the increase in ATP synthesis, there is signaling to the nucleus stimulating the production of antioxidant enzymes, proteins that stabilize cellular function and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The laser light emitting at the visible red spectrum stimulates the respiratory chain in cells under stress, leading to alterations in electron transport by mitochondria. 16,17,19,22,25 Then, besides the increase in ATP synthesis, there is signaling to the nucleus stimulating the production of antioxidant enzymes, proteins that stabilize cellular function and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals are highly unstable and exhibit remarkable ability to react with other organic substances 7 and may even cause damage to cellular DNA. 7,8 In fact, damage to odontoblasts in vivo and fibroblasts in vitro has been reported after contact with bleaching agents. [9][10][11] Therefore, bleaching agents can release substances that lead to alteration of cellular metabolism and/or inflammation in dental pulp.…”
Section: Introductionmentioning
confidence: 99%
“…10,13 The mutagenicity of substances in in vitro systems should be analyzed carefully; these assays do not have the in vivo enzyme levels responsible for detoxification of the bleaching agents. 8 Animal models can also be used to characterize the toxic effects of bleaching substances.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, during the bleaching process, CP breaks down into H 2 0 2 and urea, which are then dissociated into oxygen, water, ammonia, carbon dioxide, 9 and reactive oxygen species (ROS) that are considered potentially carcinogenic agents able to cause damage to proteins and changes in the cell nucleus. 10 Thus, there is a gap in the literature on the real genotoxicity of dental whitening agents in humans.…”
Section: Introductionmentioning
confidence: 99%
“…There are some studies investigating the genotoxic potential of dental bleaching agents. Our own studies have demonstrated that six commercial dental bleaching agents (Clarigel Gold -Dentsply; Whitespeed -Discus Dental; Nite White -Discus Dental; Magic Bleaching -Vigodent; Whiteness HP -FGM and Lase Peroxide -DMC) were genotoxic using mouse lymphoma cells or Chinese ovary hamster cells in vitro (6,7). Toothpastes containing whitening products were also found to be genotoxic using human gingival cells in vitro (8).…”
Section: Dental Bleaching Agentsmentioning
confidence: 99%